PENGENDALIAN KEBAKARAN HUTAN OLEH MASYARAKAT PEDULI API (MPA) DI TAMAN NASIONAL GUNUNG CIREMAI - Fadillah, Nurul; Basuni, sambas; Sunarminto, Tutut (Department of Forest Resources Conservation and Ecotourism - IPB University, 2016)
Mount Ciremai National Park (TNGC) is a National Park (TN) which has enormous ecological functions, especially as a water catchment area. Forest fires in TNGC occur every year and fluctuated from year to year. Forst fires destroy ecosystems and interfere the function of TNGC. Anti Fire Community (MPA) is a partnership which consist of local communities involved in forest fire control. Community partnership will never succeess without the MPA’s participation. The research objectives are to describe the perception and participation of MPA on the forest fires control in TNGC and the implementation of MPA policies. This research method is done by questionnaires, observation and interviews. The results showed that MPA positively perceive that dry season as supporting factors and community activities that involve a fire as direct factors of forest fires. The public perception is not always in line with the participation. A strong perception does not guarantee a high participation, it might be the opposit (low participation). The highest MPA’s participation in forest fires control is in forest fighting activities. Affecting factors on MPA's participation in forest fire control activities are economic factors ie wage, logistics dan goods. Occuring gap between the ideal conditions and real conditions is 80,95 percent. Perceptions which is not in line with the participation and the emerge gap is suspected to cause unoptimized of forest fire control conducted by MPA in TNGC. Keywords: forest fire control, gap, MPA, particiation, perception